Analisis Efisiensi dan Kehilangan Air pada Jaringan Irigasi Daerah Irigasi Sekampung Bunut - Utami, Elok Budi; Kusumastuti, Dyah Indriana; Winarno, Dwi Joko (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
Considering the bad impact of water loss which has an impact on its efficiency, the authors are interested in analyzing the efficiency and water loss in irrigation networks in the Sekampung Bunut Irrigation Area (DI). Efficiency and water losses were analyzed using the in-discharge discharge method. The data used in this analysis consist of primary data in the form of flow velocity data with current meters, irrigation channel cross-sections, temperature data, humidity data, then secondary data, namely data on the length of solar radiation and wind speed data. Loss of water in the secondary irrigation channel KR Irrigation Area (DI) of Sekampung Bunut lost an average of 17.15%. Meanwhile, the efficiency of the secondary channel in the Irrigation Area (DI) of Sekampung Bunut was 82.85%. The theoretical value of the average efficiency in the secondary channel KR is 90%. This shows that the amount of efficiency is still below the requirements of theoretical efficiency. One of the factors that cause water loss in the secondary channel in the Sekampung Bunut Irrigation Area is the evaporation factor that occurs along the irrigation channel. Keywords: Channel efficiency, water loss, water discharge.